Neoliberal Authoritarianism: An Ethnography of Russian Universities - Gataulina, Iuliia; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
(3z(BTh(is) book investigates a timely and important topic in contemporary world politics: the entanglements between the neoliberal and authoritarian modes of governance.(3y (B(Pinar Donmez, Senior Lecturer in International Relations at De Montfort University, Leicester) (3z(BBy detailing how Russian academic institutions increasingly blend neoliberal and authoritarian logics, this highly original book sheds considerable light on developments currently taking place around the world, including Turkey, Hungary, the United States.(3y (B(Isaac Kamola, Associate Professor of Political Science, Trinity College, Hartford) (3z(BContrary to the democratization argument advanced for years in the literature on post-communism, this book demonstrates how neoliberal reforms can reinforce, rather than curb, authoritarian control.(3y (B(Katarzyna Kaczmarska, Senior Lecturer in Politics and International Relations from the University of Edinburgh) This open access book delves into the politics of oppression and dispossession driven by global neoliberalism and state authoritarianism. Challenging liberal biases, it introduces the concept of "neoliberal authoritarianism," highlighting how the Russian state has transformed within the context of neoliberal globalization into a new state formation where authoritarianism is reinforced by neoliberal rationalities. The book analyzes neoliberal authoritarianism through an ethnographic lens on universities and their governance, which have become a new frontier of neoliberal economic development, serving the imperatives of growth and competition. Iuliia Gataulina is Postdoctoral Researcher at Tampere University, Finland. Currently, she is a member of the (3z(BInternational Political Economy(3y (Bresearch group. Her main research interests spring around international political economy, the workings of global capitalism and neoliberalism across East/West divide, and ethnographic methods in International Relations.s
Chapter 1. Introduction -- Chapter 2. University in crisis: Neoliberalization -- Chapter 3. De/re/composing neoliberalization and authoritarianism: Assemblages and ethnography. Chapter 4. Neoliberal competition and neo-imperial aspirations: University status -- Chapter 5. Eurocentricity and Russian search for sovereignty: The Bologna Process -- Chapter 6. Accelerating speed: Optimized academic labor -- Chapter 7. Academic efficiency and authoritarian governance in contamination: Performance-based pay -- Chapter 8. Life in the ruins: Alternative academic projects -- Chapter 9. De/re/composing: Conclusions.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Political sociology; Identity politics; International economic relations; Political science -- Philosophy; Political science; Political Sociology; Identity Politics; International Political Economy$1 (B.s; Political Philosophy; Political Theory